Precise and Robust crane boom tip localization using a 24 GHz radar tachymeter - Reustle, Christoph; Shmakov, Denys; Röhr, Sven; Vossiek, Martin (9th German Microwave Conference, GeMiC 2015, 2015)
This paper presents a novel radar tachymeter for safety-critical applications, using the ISM 24 GHz band for distance and angular measurements to an active target. The demonstrator system localizes the boom tip of a mobile crane during operation. This is used to determine the current working radius, in order to prevent the crane from tipping. Applying a frequency-modulated continuous-wave secondary radar concept ensures operation in the severe multipath environment typical for this type of crane. The angle of arrival is estimated using 8 receive channels in a single-input multiple-output (SIMO) configuration. Mounted at the heel section of the long telescopic boom, the tachymeter measures distance and angle with a rootmean-square error of 2.2 cm and 0.16°, respectively - showing the outstanding reliability and precision of the presented system.
Keywords: direction-of-arrival estimation; distance measurement; FMCW; position measurement; Radar applications